PENGAPLIKASIAN ILMU-ILMU UI UX PADA WEBSITE MUSEUM TAMAN TINO SIDIN - Koeswoyo, Moh.Taufiq; Mustaqim, Karna (Kohesi: Jurnal Sains dan Teknologi, 2024)
User Interface (UI) and User Experience (UX) are crucial elements that impact the success of digital platforms by enhancing user engagement and satisfaction. UI focuses on visual aspects such as layout, color, and design to make the platform aesthetically appealing. Meanwhile, UX emphasizes ease of use, smooth Navigation, and overall user satisfaction. High-quality UI/UX can strengthen user attraction and loyalty. The Museum Taman Tino Sidin in Yogyakarta, Indonesia, which showcases the works of artist Tino Sidin, lacks an official website, limiting information dissemination and hindering efforts to attract visitors. This study aims to design the UI/UX of the museum’s website to improve its online presence, facilitate the distribution of information about events and exhibitions, and ultimately increase visitor numbers. User Interface (UI) dan User Experience (UX) adalah elemen penting yang mempengaruhi keberhasilan platform digital dengan cara meningkatkan keterlibatan dan kepuasan pengguna. UI berfokus pada aspek visual seperti tata letak, warna, dan desain yang membuat platform menarik secara estetika. Sementara itu, UX berfokus pada kemudahan penggunaan, navigasi yang lancar, dan kepuasan pengguna secara keseluruhan. Kualitas UI/UX yang baik dapat memperkuat daya tarik dan loyalitas pengguna. Museum Taman Tino Sidin di Yogyakarta, Indonesia, yang menampilkan karya seniman Tino Sidin, tidak memiliki website resmi, sehingga informasi tentang museum terbatas dan upaya menarik pengunjung menjadi terhambat. Penelitian ini bertujuan untuk merancang UI/UX website museum agar meningkatkan kehadiran online, mempermudah penyebaran informasi tentang acara dan pameran, serta meningkatkan jumlah pengunjung.